PCSK9 Inhibitors: From Nature’s Lessons to Clinical Utility - Raal, Frederick J.; Chilton, Robert; Ranjith, Naresh; Rambiritch, Virendra; Leisegang, Rory F.; Ebrahim, Iftikhar O.; Tonder, Alet v.; Shunmoogam, Nelusha; Bouharati, Célia; Musa, Moji G.; Karamchand, Sumanth; Naidoo, Poobalan; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors are a novel class of non-statin lipid lowering therapy that reduce LDL-cholesterol by 50 - 60%. PCSK9 inhibitors decrease LDL-cholesterol by preventing intracellular degradation of LDL receptors; subsequently, a greater number of LDL-receptors are available on the cell surface to extract circulating LDL. Objective: To describe the origins of PCSK9 inhibitors and their current use in clinical practice. Methods: We performed a narrative review of the PCSK9 inhibitor class of drugs. Results: Current data indicate that PCSK9 inhibitors effectively reduce LDL-cholesterol and are well tolerated and safe. PCSK9 inhibitors have also been shown to reduce cardiovascular event rates in patients with stable atherosclerotic cardiovascular disease and in patients with a recent (up to one year) acute coronary syndrome. Given the costs, chronicity of the treatment and the potential budget impact, PCSK9 inhibitors are often limited to patients with the highest absolute risk for major adverse cardiovascular events despite optimal treatment with high-intensity statin and ezetimibe. Conclusion: PCSK9 inhibitors have a favorable safety, efficacy and tolerability profile. Postmarketing safety surveillance and real-world studies are needed to further support the long-term safety profile of this class of medicine.
Keywords: PCSK9 inhibitors